Evidence of WNV infection in migratory birds passing through Xinjiang, China, using viral genome amplicon approach - Tao, Kunsheng; He, Chan; Zhang, Tong; Xiao, Changguang; Du, Lifei; Li, Zongjie; Shao, Donghua; Wei, Jianchao; Li, Beibei; Qiu, Yafeng; Ma, Zhiyong; Liu, Ke (Frontiers in Microbiology, 2025)
The West Nile virus (WNV) is a mosquito-borne virus of the Flaviviridae family that is transmitted through the mosquito-migratory bird-mosquito cycle. Currently, WNV infection is widespread in the Americas, Europe, and Africa, and is one of the most important global epidemic infectious diseases. Although migratory birds play an important role in the spread of WNV, monitoring of migratory birds carrying the WNV remains limited. Here, we developed a new nucleic acid test for detecting migratory birds carrying WNV, which uses amplicons of WNV to test fecal samples from migratory birds. This new method was validated by using full-length WNV genomic plasmid. With this amplicon method, we tested the migratory bird droppings collected in different locations. The results indicated that the positive rate of WNV nucleic acid in migratory bird droppings was over 39%, which provides clues to the fact that migratory birds may carry the WNV in Xinjiang, China.